The Relationship between Analogy and the Grammatical Rule - Albib, Ibrahim; Barbahan, Hekmet (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This paper tries to examine the relationship between analogy and the grammatical rule. Analogy is one of the basic principles and bases of Arabic grammar during times of rule formation and judging it. Linguists were divided in their attitude to analogy, with some supporting it and others against it. Grammarians were more inclined toward analogy than compilers, because grammarians’ research was based on the existing similarity between words, phrases, and style used in speech reported by tellers of what had been said by the Arabs. They based their rules and origins of analogy on that similarity. Analogists transliterated some foreign terms, Arabized, and derived new words out of them in a manner similar to that done with Arabic terms. However, some grammarians went very far in their excessive use of analogy to the extent that it becomes far removed from linguistic reality to be a form riddle and guessing, leading to reaction against analogy then against grammar. Analogy became an end in itself; it overlooked its original purpose; was then manifested in rule formation of words said spontaneously.